Parasites in reineta (Brama australis) marketed in the Maule Region, Chile - Machuca, Álvaro (2021)
The aim of this study was to determine the presence of parasite larvae of zoonotic importance in reineta (Brama australis) and marinated fish (“ceviche”) prepared with this species, sold in south-central Chile (city of Talca). In total, 27 whole non-eviscerated fish were acquired from the coastal area near the city of Talca and sold in the same city; besides, 48 portions of ceviche were obtained from formal and informal local vendors. All samples were analysed macroscopically and then by enzymatic digestion. Anisakid larvae were not detected in the ceviche portions or in the fresh fish; however, the presence of cestode larvae of the genus Hepatoxylon was detected in 24 fish (88.9%), with a mean abundance of 1.9 larvae.